Kontribusi Manajemen Lingkungan Bahasa Terhadap Peningkatan Mutu Pembelajaran Bahasa Arab di Pondok Pesantren Darul Huffadh Tuju-Tuju Kajuara Kabupaten Bone - Wardana, Wardana; Rasmi, Muh (IAIN Bone, 2025)
This study aims to examine the contribution of language environment management to improving the quality of Arabic language learning at the Darul Huffadh Tuju-Tuju Kajuara Bone Islamic boarding school. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation, and analysed inductively through reduction, presentation, and conclusion drawing techniques. The results of the study indicate that the creation of an Arabic language environment (bi'ah 'arabiyyah) is carried out systematically through programme planning, organisation of the Language Advisory Council (LAC) structure, implementation of language activities, and continuous evaluation. The contribution of language environment management includes improving istima’, kalam, qira’ah, and kitabah skills; increasing students' motivation and confidence; shaping a disciplined character and love for the Arabic language; and integrating formal and non-formal learning. Supporting factors include leadership commitment, student involvement, availability of facilities, and a religious pesantren culture. Meanwhile, inhibiting factors include variations in student backgrounds, limited teaching staff, low language awareness, and time constraints. These findings are in line with behaviourism theory (Skinner, 1953) and social learning theory (Bandura, 1986), which emphasise the importance of the environment in shaping behaviour and language acquisition. This study recommends strengthening the institutionalisation of LAC, a differentiated approach, language awareness campaigns, and the integration of language programmes with the curriculum. Thus, Arabic language environment management has proven to be effective in improving the quality of learning and shaping a generation of students who are communicative, religious, and globally competitive